Hailey Hailey disease: a case report - Iffat Hassan; Abid Keen (Our Dermatology Online, 2012)
Hailey Hailey disease or Familial chronic benign pemphigus is a rare autosomal dominant acantholytic disease, clinically characterized by flaccid bullae and erosions in the intertriginous areas, mainly the axillary and inguinal region. We herein report a case of a forty year old female belonging to ethnic Kashmiri population with clinical and histopathological features suggestive of Hailey Hailey disease.